2001
DOI: 10.1007/s004320100267
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of aspirin on the growth of C6 rat glioma and on time of development of ENU-induced tumors of the nervous system

Abstract: The growth-promoting effects of high doses of ASA found in the present study in both transplanted and chemically-induced brain tumors, might be due to the blockage of autocrine inhibitory factors dependent on the cyclooxygenase pathway or by increased vascular permeability and blood supply to the tumor due to inhibition of platelet aggregation. In contrast, the inhibition of tumor growth obtained with low ASA doses in transplanted glioma might be due to different mechanisms such as the induction of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Because of the increased risk for intratumoral hemorrhage, antiplatelet drugs may not be a good solution. Nevertheless, Arrieta et al 55 treated C6 glioma-bearing rats with acetylsalicylic acid (ASA) and found a reduction in tumor size after administration of low-dose ASA, although higher doses seemed paradoxically to promote tumor growth. Other groups have also investigated the influence of inhibitors of the arachidonic acid metabolism on tumor cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increased risk for intratumoral hemorrhage, antiplatelet drugs may not be a good solution. Nevertheless, Arrieta et al 55 treated C6 glioma-bearing rats with acetylsalicylic acid (ASA) and found a reduction in tumor size after administration of low-dose ASA, although higher doses seemed paradoxically to promote tumor growth. Other groups have also investigated the influence of inhibitors of the arachidonic acid metabolism on tumor cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly indicates that the interplay of platelets and endothelial cells occurs in part via integrins mediating cell–cell adhesion. Paradoxical effects of platelet inhibition were reported by Arietta et al ., as high doses of ASA (200 or 400 mg/kg per day) increased tumor volume, cell proliferation, vascular density and mitotic index, while low doses (12.5 or 25 mg/kg per day) diminished tumor size in Wistar rats harboring glioma tumor grafts 164. However, it cannot be ruled out that ASA also had direct effects on tumor growth.…”
Section: The Role Of Platelets In Local Disease—tumor Growth and Tumomentioning
confidence: 97%
“…83 As early as 1988, Farrell et al 84 reported an effect of ibuprofen on tumor weight at high and low doses in a C6 spheroid glioma implantation model. Arrieta et al 85 studied multiple doses of acetylsalicylic acid (ASA) ranging from 12.5 to 400 mg/kg per day on the growth of C6 glioma implanted subcutaneously. A paradoxical result was observed.…”
Section: Cox-2 Expression and Inhibition In Gliomamentioning
confidence: 99%
“…The authors concluded that at higher doses, ASA may block certain autocrine inhibitory factors dependent on the cyclooxygenase pathway, whereas at lower doses, mechanisms of apoptosis may be induced. 85 Malignant glioma also expresses an increased amount of thromboxane and prostaglandin. The capacity of arachidonic acid synthesis has been shown to directly correlate with the percentage of cells in the S phase in culture.…”
Section: Cox-2 Expression and Inhibition In Gliomamentioning
confidence: 99%